Four Maternal Characteristics Determine the 12-Month Course of Chronic Severe Postpartum Depressive Symptoms - Fisher, Sheehan D. (Depress Anxiety, 2019)
BACKGROUND: Postpartum depression is a heterogeneous disorder in phenotype and etiology. Characterizing the longitudinal course of depressive symptoms over the first year after birth and identifying variables that predict distinct symptom trajectories will expedite efficient mental health treatment planning. The purpose was to determine 12-month trajectories of postpartum depressive symptoms, identify characteristics that predict the trajectories, and provide a computational algorithm that predicts trajectory membership. METHODS: A prospective cohort of women delivering at an academic medical center (2006–2011) was recruited from an urban women’s hospital in Pittsburgh, PA. Women with a postpartum depressive disorder (n=507) participated and completed symptom severity assessments at 4–8 weeks (intake), 3 months, 6 months, and 12 months. Women were predominantly Caucasian (71.8%), married (53.3%), and college educated (38.7%). Clinician interviews of depressive symptom severity, medical and psychiatric history, assessment of function, obstetric experience, and infant status were conducted. RESULTS: Analyses resulted in identification of three distinct trajectories of depressive symptoms: 1) gradual remission (50.4%), 2) partial improvement (41.8%), and 3) chronic severe (7.8%). Key predictive characteristics of the chronic severe versus gradual remission and partial improvement trajectories included parity, education, and baseline global functioning and depression severity. We were able to predict trajectory membership in with 72.8% accuracy from these characteristics. CONCLUSIONS: Four maternal characteristics predicted membership in the chronic severe versus gradual remission and partial improvement trajectories with 72.8% accuracy. The trajectory groups comprise clinically relevant subgroups with the potential for tailored treatments to reduce the disease burden of postpartum depression.